TEACHING HIGHER MATHEMATICS BASED ON COMPETENCE-BASED AND THESAURUS APPROACHES - Kushmurotov, Umurbek (Physical and Mathematical Education, 2023)
Formulation of the problem. The requirement to increase the level of mathematical training of future engineers and reduce the number of hours devoted to teaching higher mathematics gives rise to the task of developing and improving the methodology for teaching higher mathematics. The purpose of this article is to describe the methodology for teaching higher mathematics based on the thesaurus approach. Materials and methods. The research materials are pedagogical and methodical literature, and experiences of foreign and domestic scientists. In the course of the study, general scientific methods (analysis, synthesis, concretization, systematization, and generalization) were used. Results. The thesaurus approach to learning helps to clarify the mathematical competence of a particular topic, the basis of educational information is the educational thesaurus, the student’s lexicon necessary for the optimal distribution of educational information by type of training session and the development of didactic materials, the choice of methods and forms of education. Conclusions. Determining the content of the educational thesaurus of a specific topic of higher mathematics helps to clearly describe the mathematical competencies of the relevant topic, the stages of its formation, analyze and clarify the necessary educational information, distribute it by type of lesson (lecture, practical lesson, self-study). Determining the student’s vocabulary necessary for mastering a new topic helps to determine the methodology and means of teaching, in particular, to develop auxiliary tasks and questions for updating the student’s vocabulary, to establish successive links between the educational thesaurus and the student’s vocabulary, to implement a differentiated approach to learning. The proposed methodology has the properties of flexibility, additions, and modifications depending on the learning objectives and specific academic group. Further research is needed on the effective use of the thesaurus approach in the process of teaching higher mathematics.